Mock up technique and anatomical caps stratification - Lamas Lara, César (2011)
Patient´s aesthetic requirements are increasing and this demands the greatest professional preparation to provide the best treatment option. The materials for use in dentistry and restorative techniques have evolved very quickly. Composite resins give us an alternative treatment in the anterior sector because they have good aesthetic and mechanical properties. With the evolution of the composite resins we can achieve very natural restorations doing them better and better. This article details Mock Up’s technique and reconstruction by anatomical stratification in the resolution of a case. The aim was to restore aesthetics and function to anterior sector. The results were satisfactory for the patient obtaining this way the naturalness and recovery of lost function in the anterior sector. It can be concluded that the knowledge of restorative materials as well as various techniques are essential for a proper restoration.